Accuracy Limitations of Fast Mechanical Probing - van Vliet, W.P.; Schellekens, P.H. (CIRP annals, 1996)
Although dynamic errors of CMMs are getting more attention now, still little is published about the dynamic disturbances acting on mechanical probe systems. The process of mechanical probing is subject to dynamic influences, even at generally accepted low measurement velocities. It will be shown that due to the nature of the mechanical probing principle, impact forces are much higher than measurement forces and can result in considerable damage of workpiece surfaces. Further it is proved that the relation between the position of the probe tip and the workpiece position during impact cannot be determined unambiguously due to bouncing, irrespective of the probe construction. Consequently measurement accuracy can be lost, depending on the principle of probing. Analysis shows that this bouncing effect cannot be avoided during probing and therefore should be taken into account to improve probe performance. Measurement results obtained with two different probe systems will be presented to illustrate those impact phenomena. Based on these results recommendations for probe system design are given in order to speed-up probe operation without degradation of probe performance.